Study on the Effect of Inclination Angle on Heat Transfer Enhancement of a Ferrofluid and Kerosene in a Closed Loop Oscillating Heat Pipe - et. al., Dr. V. Rambabua, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper elaborates on the findings of study on the effect of Fe2O3/Kerosene nanofluid to the copper closed-loop oscillating heat pipe under the magnetic field for inclination angles ranging from 0° to 90° under different heat inputs (10–90 W). The heat pipe’s heat transfer coefficient was measured without and with the magnetic field. Moreover, the vapor temperature was assessed directly at the center of the oscillating heat pipe by exposing the ferro-nano particles to a magnetic field. It was shown that Fe2O3 nanoparticles could improve the thermal resistance and subsequently thermal performance as well as the pipe’s heat transfer coefficient, especially under the magnetic field. The heat pipe’s heat transfer coefficient increased as the input heat flux increased. The results also demonstrated that the heat pipe’s inclination angle had a significant effect on performance of heat pipe. The critical angle was 75° as the heat transfer coefficient increased due to higher inclination angle.